REINTERPRETASI BUDI PEKERTI DALAM KONSTELASI KEBUDAYAAN JAWA DAN JEPANG - Agus Maladi Irianto (Universitas Diponegoro, 2013)
Abstrak This article discusses about the cultural resistance which starts from the character that forms a set of norms which refers to the character and ideal behavior of its community supporters. Javanese People and Japanese people have developed the concept of character from generation to generation through the orientation of every action, as well as becoming values which inherent with the background of each cultures. In line with the recent global era, reinterpretation of Javanese culture and Japanese culture becomes one of strategJies to develop each cultural resistance. Javanese people respond the global mainstream as moral threat as local wisdom, meanwhile Japanese people respond the global era as a form to establish the nationality spirit. The influence of globalization for Javanese people has created expressions of violence, hedonic, and the loss of family atmosphere. For Japanese people, globalization is precisely becoming the starting point of the cultural diplomacy. Key words: character, reinterpretation, globalization, Javanese culture, Japanese culture